Pengentasan Stunting di Lombok Barat Untuk mencapai Sustainable Development Goals Ketiga - Masyeni, Sri; Yuniekawati, Yuyun; Lestarini, Ima Arum; Kadriyan, Hamsu; Sahadewa, Sukma; Rismawaty, Ika; Pinatih, Januartha Putra; Asparini, Ruby Riana (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Background: Stunting, a global issue, is being addressed by the World SDGs program, which has identified stunting alleviation as a key focus. Objectif: To enhance partner understanding of stunting, its treatment, and prevention. Methods: The community service method involves socialization through focus group discussions, counseling, and evaluation. Results: 100% of partners demonstrated an increase in their knowledge about stunting, with the average pretest score at 27 and the average posttest score at 83. Conclusion: Counseling, a practical and effective tool, significantly enhances knowledge about stunting.